Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/10732748211038736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Cancer-Related Hospitalizations in Brazil

Abstract: Background Alongside the SARS-CoV-2 (COVID-19) pandemic, Brazil also faces an ongoing rise in cancer burden. In 2020, there were approximately 592 000 new cancer cases and 260 000 cancer deaths. Considering the heterogeneities across Brazil, this study aimed to estimate the impact of the COVID-19 pandemic on cancer-related hospital admissions at a national and regional level. Methods The national, regional, and state-specific monthly average of cancer-related hospital admission rates per 100 000 inhabitants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 31 publications
4
17
0
5
Order By: Relevance
“…Similarly, the number of cancer patients seeking traditional Chinese medicine treatment increased by approximately 50% during the COVID-19 outbreak in Taiwan, China (17). The observed trend regarding admissions due to cancer care during the outbreak is consistent with reports from Brazil (18) and the UK (8). Previous evidence has shown that a decrease in cancer patients seeking treatment may have negative effects on their survival and mortality in the near future (19).…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, the number of cancer patients seeking traditional Chinese medicine treatment increased by approximately 50% during the COVID-19 outbreak in Taiwan, China (17). The observed trend regarding admissions due to cancer care during the outbreak is consistent with reports from Brazil (18) and the UK (8). Previous evidence has shown that a decrease in cancer patients seeking treatment may have negative effects on their survival and mortality in the near future (19).…”
Section: Discussionsupporting
confidence: 78%
“…Social distancing strategies have affected patient management in health services, resulting in a lower demand for access to health services, reduced number of appointments, and suspension of care activities, elective primary care, and highly complex health procedures. Additionally, overwhelming of health services by patients suspected of having COVID-19 have compromised the care and treatment of patients with NCDs, especially in low-and middle-income countries [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Delays in screenings or non-urgent medical visits may reduce the rate of early disease detection, and patients with chronic diseases are more likely to experience severe complications if treatment is delayed or discontinued [29] , [30] , [31] . Several studies reported that reductions in cancer screening have a considerable impact on cancer incidence and prognosis [19] , [22] , [30] . A study that simulated the interruption of colorectal cancer screening programs worldwide during the COVID-19 pandemic found that even if screening is reduced or stopped for only six months, colorectal cancer deaths may increase by 0.4-1.0% for 30 years to 2050 [7] .…”
Section: Discussionmentioning
confidence: 99%
“…However, although COVID-19 may have a significant impact on healthcare utilization in the general population, early studies focused on the impact of COVID-19 on the healthcare utilization of infected patients, such as hospitalizations or ICU admissions [14] , [15] , [16] . Most previous studies investigated only on restrictions on the healthcare utilization of specific population groups [17] , [18] , [19] . Although there were studies on general population, most of the studies are on specific situations such as specific screening or emergency care [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%